Практичні аспекти визначення ефективності розробок електротехнічної продукції - Александров, Віталій Володимирович (НТУ "ХПІ", 2016)
В статті приділена увага практичним аспектам оцінки економічної ефективності розробок електротехнічної продукції. Розглянуто існуючі проблеми практичного застосування існуючих теоретичних методик оцінки ефективності на етапі відбору до виробництва нової техніки. На основі практичного досвіду розрахунків економічної ефективності виробів запропоновано для попередньої оцінки ухвалення рішення про виробництво застосовувати розрахунки показників економічного ефекту у виробника, економічного ефекту у споживача та дисконтовані показники економічної ефективності.

The article deals with the practical assessment of the economic efficiency development of electrical products. Currently existing theoretical techniques are complicated in practical use. Proposed by scientists methods have been studied and describes their shortcomings. On the basis of practical significance were selected indicators of economic benefit from the manufacturer, the economic effect of the consumer and the present indicators of economic efficiency. Estimation of economic efficiency of product development can be carried out using traditional indicators: the present value of "cash flow"; net present value; payback period; the rate of return (profitability). The article details the method for calculating these indicators. These evaluation methods do not require too high craftsmanship. It is an integral part of their positive aspect. Most of the calculations of a preliminary assessment of prospects for the production can be made in terms of economic benefit the producer and the consumer. More detailed calculations in terms of discounted cash flows is performed, if necessary, to attract investment funds and justification of the business plan the release of new products. To date, the proposed methods can easily be utilized of the enterprise managements, because they do not require special training on the economic specialty.
Practical aspects of determining the efficiency of electrical products development
Keywords: економічна ефективність; оцінка; електротехнічна продукція; економічний ефект; виробник; споживач; дисконтовані показники; грошовий потік; інвестиції; норма прибутку; дисконтована рентабельність; чиста дисконтована вартість; economic evaluation; electrical products; economic effect; manufacturer; consumer; discounted indicators; cash flow; investment rate; discounted return; net present value